Existence of nonnegative solutions for a fractional parabolic equation in the whole space
UDC 517.9 We study existence of nonnegative solutions for a parabolic problem ut = - (-)^α2 u + c|x|^α u in R^d× (0, T). Here 0, number=8, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Kenzizi, T., year=2019, month=Aug., pages=1064–1072